C♯ 3.0 with the .NET Framework 3.5 unleashed - Mayo, Joseph (Sams, 2008)
Whether you need an approachable on-ramp to .NET or you want to enhance your skills, C# 3.0 Unleashed is a comprehensive, in-depth guide to the solutions you seek. You'll learn to do more with the new tools that are available, including Visual Studio 2008 and the .NET Framework Class Libraries. Throughout this book, you'll get a practical look at what can be the most useful tools for any given task. You'll also learn common traps to avoid and learn insightful tips that will save you time and help you be more productive. C# 3.0 Unleashed contains complete coverage of the C# programming language. The author covers all the essential syntax, but keeps the focus on practical application. The chapters are arranged to take you step-by-step from the core of the C# language to elements of the .NET Framework, and further into advanced concepts on distributed n-tier Internet applications. Additionally, C# 3.0 Unleashed shows you how to debug, monitor, and scale enterprise applications, enabling you to use the C# programming language to ship the right code at the right time. What's included in this book: A complete reference for C# syntax, object oriented programming, and component programming with C# Comprehensive data coverage through ADO.NET and LINQ An introduction to UI technologies, including Windows Forms, WPF, ASP.NET Ajax, and Silverlight Coverage of traditional ASMX and WCF Web Services Coverage of multiple .NET technologies, including networking, instrumentation, interop, and multi-threading In-depth discussion of platform concepts including CLR, Garbage Collection, Type System, Assemblies, and Code Access Security Guidance on design and architecture for a big-picture view and essential help in piecing together all you've learned.
Print version record
Keywords: Microsoft .NET Framework; C# (Computer program language); C# (Langage de programmation); C♯ (Computer program language)